Integracja międzypokoleniowa przedszkolaków z seniorami cz. I. Opinie osób starszych = Intergenerational integration between preschool children and elderly people Part I. Opinions of the elderly - Bąk, Jadwiga; Chrzan, Agnieszka; Świrszcz, Anna; Pietraszek, Agata; Kachaniuk, Hanna; Charzyńska-Gula, Marianna; Łuczyk, Marta (Journal of Education, Health and Sport, 2016)
Bąk Jadwiga, Chrzan Agnieszka, Świrszcz Anna, Pietraszek Agata, Kachaniuk Hanna, Charzyńska-Gula Marianna, Łuczyk Marta. Integracja międzypokoleniowa przedszkolaków z seniorami cz. I. Opinie osób starszych = Intergenerational integration between preschool children and elderly people Part I. Opinions of the elderly. Journal of Education, Health and Sport. 2016;6(9):498-505. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.154157 http://ojs.ukw.edu.pl/index.php/johs/article/view/3857 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 16.09.2016. Integracja międzypokoleniowa przedszkolaków z seniorami cz. I. Opinie osób starszych Intergenerational integration between preschool children and elderly people Part I. Opinions of the elderly Jadwiga Bąk1, Agnieszka Chrzan1, Anna Świrszcz1, Agata Pietraszek2, Hanna Kachaniuk3, Marianna Charzyńska-Gula4, Marta Łuczyk2 SKN przy Katedrze Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie Zakład Onkologii, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie Zakład Medycyny Rodzinnej i Pielęgniarstwa Środowiskowego, Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie Wydział Nauk Społecznych i Humanistycznych, Państwowa Wyższa Szkoła Zawodowa im. prof. Stanisława Tarnowskiego w Tarnobrzegu Streszczenie Cel pracy. Celem pracy było poznanie i opisanie opinii seniorów na temat organizowania wspólnych zajęć przedszkolaków z seniorami, których byliby potencjalnymi uczestnikami. Materiał i metody. Metodą badawczą był sondaż diagnostyczny z techniką ankiety. Badania przeprowadzono wśród 135 seniorów w wieku do 90 r.ż. uczestniczących w zajęciach Uniwersytetów Trzeciego Wieku w Lublinie i Wadowicach. Wyniki: Ponad 80% ankietowanych przyznało, że lubi dzieci w wieku przedszkolnym. Większość badanych seniorów przyznało (81,5%), że chciałoby, aby organizowano wspólne spotkania dla dzieci w wieku przedszkolnym oraz osób starszych. Zdecydowana większość, bo nawet 90% badanych, którzy odpowiedzieli pozytywnie na to pytanie spotykałoby się z dziećmi nieodpłatnie. Rodzaje aktywności, które seniorzy chętnie realizowaliby razem z dziećmi to przede wszystkim czytanie książek i spacery. Jeden na ośmiu (12,7%) seniorów mógłby poświęcić czas przedszkolakom do 30 min. dziennie, a ponad połowa (58,1%) mogłaby poświęcić od 1-2 godzin dziennie. Głównym powodem chęci spotykania się z dziećmi byłoby dla badanych seniorów spełnienie poczucia bycia potrzebnym. Wnioski: Badani seniorzy w większości deklarują chęć uczestnictwa w spotkaniach integracyjnych z młodym pokoleniem. Może być to wyraźny sygnał wskazujący na potrzebę organizacji tego typu przedsięwzięć. Osoby starsze posiadają mądrość życiową oraz doświadczenie, z którego społeczeństwo powinno korzystać i przekazywać ją młodym pokoleniom. Słowa kluczowe: starzenie się, integracja społeczna, rozwój dziecka Abstract Objective. The objective of the study was to identify and describe the opinions of seniors on organising activities for preschool children with the elderly as potential participants. Material and methods. The diagnostic survey method was applied, together with the questionnaire technique. The survey was carried out among 135 seniors aged up to 90 years taking courses at the Universities of the Third Age in Lublin and Wadowice. Results. Over 80% of the surveyed stated that they were fond of preschool children. Most of the seniors (81.5%) admitted that they would gladly participate in meetings with children at this age. A considerable majority, i.e. 90% of the respondents who were willing to take part in such activities would do so free of charge. The types of activities that the seniors would like to carry out together with the children were mostly reading books and going for walks. One in seven (12.7%) of seniors would be able to spend up to 30 minutes per day with preschool children, and over a half (58.1%) - 1-2 hours per day. The main reason why the surveyed elderly people were willing to meet with children was to satisfy the need to be useful. Conclusions. Most of the surveyed seniors declared their readiness to participate in integration meetings with the young generation. This may be a clear indication that such activities are needed. Elderly people have experience and worldly wisdom which society should use and share with younger generations. Key words: aging, community integration, child development